Peningkatan Kemampuan Bahasa Ekspresif terhadap Anak Usia 4-5 Tahun melalui Kegiatan Bermain Peran - Khairunnisa, Thifal Aqila; Kasih, Delina; Widiyastuti, Arie (Neolectura, 2025)
This study aims to improve the expressive language skills of children aged 4–5 years through roleplaying activities at TKIT Insan Kamil. The research employed the Classroom Action Research (CAR) method using Kurt Lewin’s model, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 20 children in group A. Based on the overall results, in the pre-cycle the children’s expressive language skills were at 33.00%, increasing to 43.00% in cycle I, and showing a significant improvement in cycle II, reaching 81.00%. Role-playing activities proved effective in encouraging children to expand their vocabulary, construct simple sentences, and build confidence in speaking. The improvement from the pre-cycle to cycle II indicates that the Classroom Action Research (CAR) method had a significant positive impact on the development of children’s expressive language skills. Thus, role- playing activities are proven to be effective in enhancing young children’s expressive language abilities by encouraging them to broaden their vocabulary, form simple sentences, and develop self-confidence in communication.